A Comparison of Efficiency of Life Insurance Companies in Mainland China and Taiwan Using Bootstrapped Truncated Regression Approach - Hwai-Shuh Shieh; Yang Li; Jin-li Hu; Yong-Ze Ang (Cogent Economics & Finance, 2022)
For strategic and competitive insights, this study measures and benchmarks the comparative operating efficiencies of insurance companies in Taiwan and mainland China. We employ the two-stage DEA with the bootstrapped truncated regression approach to examine the overall efficiency of insurance companies in Taiwan and mainland China during 2005-2011. Empirical results reveal that the savings rate, elderly population percentage, and business freedom positively affect the managerial efficiency of life insurance companies in Taiwan and mainland China, while GDP growth rate, inflation rate, corruption index, and climate risk negatively affect their managerial efficiency.
Keywords: 330; efficiency; two-stage DEA; bootstrap; truncated regression model; insuranceindustry